123k views
3 votes
Substitution method
6x-7y=5,3x+y=-1​

1 Answer

3 votes

Answer:


x = - (2)/(27)


y = - (4)/(5)

Explanation:

Lets call


6x - 7y = 5

equation 1


3x + y = - 1

equation 2

using equation 2, we would make y the subject of the formula as it would be easier


y = - 1 - 3x

This would now be called our equation 3

Now the next step is to substitute equation 3 in equation 1


6x - (7( - 1 - 3x)) = 5


6x - ( - 7 - 21x) = 5


6x + 7 + 21x = 5


27x = 5 - 7


27x = - 2

Divide both sides by 27
(27x)/(27) = - (2)/(27)


x = ( - 2)/(27)

Substitute the value of x in equation 2


3( ( - 2)/(27) ) + y = - 1


- ( 2)/(9) + y = - 1


y = - 1 + (2)/(9)


y = - ( 8)/(10)


y = - (4)/(5)

User Aleksandar Totic
by
5.2k points